Comportamento mecânico de um modificador de conexão protética (MCP) para implante dental - Loureiro, Karine Regina Tolesano (2018)
Considering the positive aspects of Morse taper (MT) connection and searching for solutions of problems with deep implants of external hexagon implants (EH), the purpose of this study was to analyze qualitatively and quantitatively, through Scanning Electron Microscopy (SEM), Mechanical Cycling, tightening and loosening torque of prosthetic components by a digital torquemeter, Optical Microscopy (OM) and Digital Radiography, the use of an abutment - Prosthetic Connection Modifier (MCP), adapted to EH implants allowing its connection to be converted into a MT type. Thirty EH implants were inserted into polystyrene resin blocks and divided into two groups: MCP group formed by crown/abutmentMT/MCP/implant (n = 15) and Abutment (ABT) Group formed by crown/abutmentEH/implant (n = 15), five specimens from each group composed the control group that was not submitted to fatigue testing. For characterization and qualitative analysis, all components were submitted to Scanning Electronic Microscopy (SEM) and Optical Microscopy (OM) before and after mechanical cycling, and for control group before and after screw loosening. To verify tightening and loosening torque, all thirty specimens were taken to the MK Control torquemeter and for the fatigue test 10 specimens of each group were subjected to mechanical cycling (1,200,000 cycles) subjected to a force of 50 N at a frequency of 2Hz with an inclination of 30 ° according to ISO 14801. For statistics evaluation a significance level of α = 0.05 was used and parametric and non-parametric tests were performed. SEM images were analyzed qualitatively and for all groups before cycling were observed machining residues and after cycling were found slight morphology discrepancies in the hexagons. After cycling, there was no occurrence of loosening or axial displacement of prosthesis evaluated by digital radiographs. After statistical evaluation among groups and intra-group, comparing the initial and loosening torque, evaluation of the mean of internal area of the hexagon and evaluation of the internal length of the circumference, statistically significant differences were observed only for the ABT Group. The MCP group did not present loosening after mechanical cycling, which means that MCP showed better results in adaptation and retention when compared to the other group and MCP presents satisfactory mechanical characteristics to its applicability.